Study of nanostructured W03. - Chuah , Lee Siang (Universiti Sains Malaysia, 2015)
In this project we have investigated and successfully revealed another method to produce this nanostructured tungsten trioxide (W03) film of several microns length using electrochemically method and nitric acid as the solution. We have 5 samples that we set the solution concentricity to be varies from 0.5 M to 2.5 M in order to find the best method among those solution concentricity. A platelet- like or stripe-like crystals with the length of 20 to 500nm were obtained after anodization of tungsten foils. All test result covers on physical, morphological, vibrational modes and structural analysis has proved that all 5 samples was able to formed a nanostructure tungsten oxide by the anodization process at a constant 60 Volts of power supply and annealed at 500°C for 2 hours.